Dispute Settlement in the Conditions of Space Commercialization (Summary) - O. A. Volynskaya (Московский журнал международного права, 2013)
Commercialization of space activities is the main tendency of development of the world cosmonautics. With the growth of a global space market the interests of the private space sector come to the fore, which increases significantly a possibility of conflicts among all space actors: states, international organizations and commercial companies. Current nonbinding dispute resolution mechanisms, first of all diplomatic settlement, are not sufficient any longer to ensure safety, security and stability of space operations.This article analyses general and specific methods of settlement of disputes arising from the exploration and use of outer space, as well as prospects of enhancing the existing dispute resolution mechanisms in International Space Law.